2018
DOI: 10.4187/respcare.06336
|View full text |Cite
|
Sign up to set email alerts
|

A High Degree of Dyspnea Is Associated With Poor Maximum Exercise Capacity in Subjects With COPD With the Same Severity of Air-Flow Obstruction

Abstract: BACKGROUND: In patients with COPD, limited data have been reported concerning the association between dyspnea perception and exercise tests. Moreover, the perception of dyspnea has not been analyzed in patients with the same severity of air-flow obstruction. The aim of our study was to evaluate the relationship between the degree of dyspnea and exercise capacity in subjects with COPD who had the same severity of air-flow obstruction. METHODS: We assessed dyspnea perception and maximum exercise capacity by usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
7
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 25 publications
(31 reference statements)
4
7
0
2
Order By: Relevance
“… 35 Moreover, low cardiorespiratory fitness mediates exercise-related symptoms, specifically increasing ratings of dyspnea in COPD. 36 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 35 Moreover, low cardiorespiratory fitness mediates exercise-related symptoms, specifically increasing ratings of dyspnea in COPD. 36 …”
Section: Discussionmentioning
confidence: 99%
“…35 Moreover, low cardiorespiratory fitness mediates exercise-related symptoms, specifically increasing ratings of dyspnea in COPD. 36 Previous research has shown that physical inactivity is an independent predictor of both CAC 37 and coronary artery diseases. 11 Yet, after adjustment for hypertension, smoking status, diabetes mellitus, and hypercholesterolemia, we found no association of current PA levels with CAC.…”
mentioning
confidence: 99%
“…(4) É importante ressaltar que pacientes com DPOC com alto grau de dispneia também podem apresentar baixa capacidade máxima de exercício associada, independentemente da gravidade da obstrução ao fluxo aéreo. (5) Além disso, a dispneia não é o único sintoma relatado por pacientes com DPOC: o estado da saúde respiratória e como a DPOC impacta esses pacientes podem incluir uma série de aspectos clínicos, melhorando a identificação dos desfechos relatados pelos pacientes. (1) Em suma, a DPOC pode afetar a percepção do paciente de várias maneiras.…”
Section: Platão Antigo Filósofo Gregounclassified
“…Полученные нами результаты свидетельствуют, что улучшению переносимости программ реабилитации пациентами с ишемической болезнью сердца сопутствует множество факторов, в частности показатели жизненной емкости легких, сердечного выброса крови, индекса массы тела. В современных научных работах на примере больных пульмонологического и кардиологического профиля изучается, как состояние дыхательной системы влияет на тренировочную выносливость пациентов [9][10][11][12]. Результаты данных исследований говорят об отрицательной переносимости нагрузок больными с низкими респираторными показателями, в том числе приведенными в нашей работе (ОФВ 1 , жизненная емкость легких).…”
Section: обсуждение основного результата исследованияunclassified